Smoothed particle hydrodynamics simulation of underwater explosions with dynamic particle refinement - Tieshuan Zhuang; Xiangwei Dong (AIP Advances, 2020)
The underwater explosion is a very complex multiphase phenomenon that poses a threat to the safety of ocean structures. Numerical simulation is of great significance in understanding the underlying mechanisms of hydrodynamics and structural damages due to underwater explosions. In this study, a mesh-free method, smoothed particle hydrodynamics (SPH), is used to establish the numerical model of underwater explosions. The computational domain consists of water and explosive gas, which is initially discretized into a series of uniformly distributed particles. To overcome the resolution difference between two phases due to the gas expansion, the dynamic particle refinement algorithm is first combined into the SPH. The particle resolution can be automatically adjusted by particle splitting techniques, thereby reducing the computation error of the gas–liquid interface. Robustness, concision, and validity of the model are validated by simulating the shock wave propagation and the bubble expansion. This study provides an effective numerical model for underwater explosion problems involving free surface flow, fluid–structure interaction, and large deformation.